2012
DOI: 10.1177/0042085912456845
|View full text |Cite
|
Sign up to set email alerts
|

“Stakes Is High”

Abstract: This article explores practitioner inquiry and culturally relevant pedagogy to create academic success with students facing high school exit examinations in Reading. In Florida, about one-third of African American students passed the test in 2010. Student perspectives on achievement, school processes, and engagement were incorporated with strategic practice to create a collaborative, classroom environment. Culturally relevant pedagogy, literacy theory, and English language arts instruction were integrated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 37 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Future research on rural school leadership in the context of African American student experiences is much needed. At present, however, most scholarship specific to principal leadership and African American student experiences are contextualized through an urban lens (Houchen, 2013). We call for a mitigation of national narratives and scholarly conversations that whitewash rurality and-by default-urbanize the schooling experiences of African American students.…”
Section: Implications and Discussionmentioning
confidence: 98%
“…Future research on rural school leadership in the context of African American student experiences is much needed. At present, however, most scholarship specific to principal leadership and African American student experiences are contextualized through an urban lens (Houchen, 2013). We call for a mitigation of national narratives and scholarly conversations that whitewash rurality and-by default-urbanize the schooling experiences of African American students.…”
Section: Implications and Discussionmentioning
confidence: 98%
“…One of the many important factors that influence the extent to which urban schools actualize their capacity to support African American educational achievement involves the instructional practices and approaches of educators (Darling-Hammond, 2010). Teachers are invaluable resources, and research has documented the impact that teacher expectations (Diamond, Randolph, & Spillane, 2004; Ferguson, 2003; Houchen, 2013; Irvine, 1990; Jackson & Wilson, 2012) and pedagogy (Cholewa, Amatea, West-Olatunji, & Wright, 2012; Griner & Stewart, 2013; Ladson-Billings, 1994/2009; Lindsey, 2015; Ware, 2006) have on African American student outcomes. In the pedagogical research, both the literature on effective pedagogy for African American children and on effective Black educators emphasize approaches to meet student needs and have found that teachers who demonstrate care and a consistent demand for excellence have a significant positive impact on African American student achievement.…”
mentioning
confidence: 99%
“…What is taught and tested in the classroom upholds a certain discourse, whether implicitly or explicitly, which can affirm the social and political power of a certain culture. Thus, it is important to acknowledge language and literature as sociopolitical to challenge the power structures within the dominant discourses taught in schools, both in the past and present (Houchen, 2012). One must be fully aware of the perceptions of different ideologies presented in literature, as well as of languages and dialects, and develop a practice of questioning the rules of grammar created by the dominant culture (Janks, et al, 2013).…”
Section: The Politics Of Literacy Educationmentioning
confidence: 99%